Identifying the Relationship Between Residential Type and Health Outcomes of the Community-Dwelling Thai Older Adults in the Baseline Analysis of a Cluster-Randomized Controlled Trial - Nadila Mulati; Myo Nyein Aung; Saiyud Moolphate; Thin Nyein Nyein Aung; Yuka Koyanagi; Siripen Supakankunti; Motoyuki Yuasa (Geriatrics)
Background/Objectives: As people age, their environment plays a critical role in shaping their health. With Thailand’s rapidly aging population, it is crucial to understand how different living environments affect the well-being of older adults. This study examines differences in biopsychosocial health indicators between older adults living in village communities and private housing estates in Chiang Mai, Thailand. Methods: A cross-sectional study was conducted using baseline data from the Community-Integrated Intermediary Care (CIIC) Service Model, a Cluster Randomized Controlled Trial in Thailand (TCTR20190412004). The study included 2788 older adults (aged 60+). Of these, 89.49% resided in village communities, and 10.51% in private housing estates. Validated instruments were used to assess health indicators. Descriptive statistics, multivariate analysis of variance, and multiple logistic regression analyses were performed. Results: Older adults in private housing estates had significantly lower odds of experiencing pain or discomfort (Adj OR: 0.64, 95% CI: 0.49–0.84) and were 1.36 times more likely to report positive perceived health. However, they had lower odds of perceiving themselves as physically and socially active (Adj OR: 0.74, 95% CI: 0.57–0.97) and were 0.30 times less likely to rate their quality of life higher (Adj OR: 0.30, 95% CI: 0.22–0.40) compared to their village community counterparts. Conclusions: The residential environment significantly influences older adults’ health and well-being. Tailored health promotion interventions should leverage the unique strengths of both village communities and private housing estates to enhance social connections, physical activity, and quality of life, promoting healthy, active aging across diverse settings.